2020
DOI: 10.55175/cdk.v47i10.1078
|View full text |Cite
|
Sign up to set email alerts
|

Manifestasi Okular Coronavirus Disease 2019 (COVID-19): Klinis dan pencegahan

Abstract: <p>Pandemi global Coronavirus Disease 2019 (COVID-19) memiliki gejala utama batuk, demam, kelelahan, sesak napas, dan gejala respiratori lainnya. Didapatkan kasus pasien COVID-19 yang memiliki keluhan okular seperti konjungtivitis. Angiotensin-converting enzyme 2 (ACE2), yang merupakan reseptor SARS-CoV-2 juga didapatkan pada sel epitel konjungtiva dan kornea manusia, sehingga memungkinkan transmisi melalui okular. Tatalaksana gejala okular pada COVID-19 hingga saat ini masih terus dikembangkan serta diu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Compared with SARS-CoV and MERS-CoV, COVID-19 is reported to have a low fatality rate. Still, previous studies reported that the number of cases of COVID-19 sufferers was almost 10 times that in the first two months of the total SARS patients (Priscilia et al, 2020); this shows that the COVID-19 virus has a very fast and widespread transmission rate. The Indonesian Kemenkes RI (2021) reports that in 2021 the COVID-19 virus with a new variant entered Indonesia; the new COVID-19 variants include B.117 from England, B.1351 from South Africa, and a double-mutated variant from India B.…”
Section: Covid-19 Prevalence Based On Conjunctiva Swabmentioning
confidence: 89%
See 2 more Smart Citations
“…Compared with SARS-CoV and MERS-CoV, COVID-19 is reported to have a low fatality rate. Still, previous studies reported that the number of cases of COVID-19 sufferers was almost 10 times that in the first two months of the total SARS patients (Priscilia et al, 2020); this shows that the COVID-19 virus has a very fast and widespread transmission rate. The Indonesian Kemenkes RI (2021) reports that in 2021 the COVID-19 virus with a new variant entered Indonesia; the new COVID-19 variants include B.117 from England, B.1351 from South Africa, and a double-mutated variant from India B.…”
Section: Covid-19 Prevalence Based On Conjunctiva Swabmentioning
confidence: 89%
“…There are 4 main protein structures in Coronavirus, namely: protein N (nucleocapsid), glycoprotein M (membrane), glycoprotein spike S (spike), and protein E (sheath) (Ministry of Health RI, 2020). COVID-19 enters human cells through the S protein on the viral envelope binding to the cell membrane receptor, namely angiotensin-converting enzyme 2 (ACE2) (Priscilia et al, 2020). ACE2 is a receptor widely found in the human body, one of which is in the eye.…”
Section: Mechanism Of Covid-19 Transmission Through Ocularmentioning
confidence: 99%
See 1 more Smart Citation